2015
DOI: 10.2147/vmrr.s77255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of fenbendazole (FBZ) and oxfendazole in alpacas (Lama pacos) after single intravenous and oral dosing of FBZ

Abstract: The objective of this study was to determine plasma pharmacokinetics and bioavailability of fenbendazole (FBZ) and oxfendazole (OFZ) after intravenous (iv) and oral administrations of FBZ (5 mg/kg) to alpacas. Plasma concentrations of FBZ and OFZ after administration of FBZ iv and orally (5 mg/kg) were determined by high-performance liquid chromatography with ultraviolet detection. Total clearance (CL) of FBZ was 16.5±4 mL/kg/min (range: 4–31 mL/kg/min), and steady-state volume of distribution (Vdss) was 3.3±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In the present study, maximum plasma FBZ concentration of 1.85 µg/ml (C max for 20 mg/kg) and 3.09 µg/ml (C max for 50 mg/kg) was comparable with the result of 1.32 µg/ml in L. rohita reported by Dar et al (2018). However, Plumb, (2002), Short et al (1987), Lakritz et al (2015 and found the peak plasma FBZ concentration of 11 µg/ ml in cattle, 0.07 µg/ml in the horse, 13 µg/ml in sheep and 0.12 µg/ ml in alpacas. The present finding revealed that FBZ is rapidly absorbed to reach peak concentration at 4 hr and remain for 96 and 120 hr after oral administration of 20 and 50 mg/kg b.wt.…”
Section: Ta B L Esupporting
confidence: 84%
“…In the present study, maximum plasma FBZ concentration of 1.85 µg/ml (C max for 20 mg/kg) and 3.09 µg/ml (C max for 50 mg/kg) was comparable with the result of 1.32 µg/ml in L. rohita reported by Dar et al (2018). However, Plumb, (2002), Short et al (1987), Lakritz et al (2015 and found the peak plasma FBZ concentration of 11 µg/ ml in cattle, 0.07 µg/ml in the horse, 13 µg/ml in sheep and 0.12 µg/ ml in alpacas. The present finding revealed that FBZ is rapidly absorbed to reach peak concentration at 4 hr and remain for 96 and 120 hr after oral administration of 20 and 50 mg/kg b.wt.…”
Section: Ta B L Esupporting
confidence: 84%
“…The pharmacokinetic population model allowed the estimation of the absorption half-life for FBZ (18.6 h) and elimination half-lives for FBZ (2.8 h) and FBZ-SO (4.3 h). The relatively faster disposition process of FBZ in contrast to the estimated absorption rate indicates the presence of flip-flop pharmacokinetics after oral administration in sheep, a phenomenon previously observed in studies assessing FBZ exposure after oral and intravenous administration in pigs and alpacas (Lakritz et al, 2015;Petersen and Friis, 2000).…”
Section: Discussionmentioning
confidence: 63%
“…Enteric reabsorption has been previously demonstrated for both FBZ and FBZ-SO (Hennessy et al, 1993). In addition, the metabolic conversion of FBZ to FBZ-SO is reversible by reductive metabolism within the rumen of sheep and cattle (Lakritz et al, 2015). Taken together, the enterohepatic cycling of FBZ-SO, produced in a higher proportion by pre-systemic metabolism after oral administration, and its conversion to FBZ, could lead to a sustained input of the latter to the systemic circulation.…”
Section: Discussionmentioning
confidence: 91%
“…The plasma concentrations of OFZ, FBZ, and FBZSO 2 were analyzed by HPLC using the modified method reported by Lakritz et al (2015). The detection of OFZ, FBZ, and FBZSO 2 in plasma was performed using a SPD‐10A UV–VIS detector set at 292 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The plasma concentrations of OFZ, FBZ, and FBZSO 2 were analyzed by HPLC using the modified method reported by Lakritz et al (2015).…”
Section: Oxfendazole Fenbendazole and Fenbendazole Sulphonementioning
confidence: 99%